2016
DOI: 10.1002/pssa.201600504
|View full text |Cite
|
Sign up to set email alerts
|

A physics‐based threshold voltage model of AlGaN/GaN nanowire channel high electron mobility transistor

Abstract: A new simple model of threshold voltage for AlGaN/GaN nanowire channel high electron mobility transistors (NC‐HEMTs) is built in this work. Firstly, four NC‐HEMTs with different nanowire channel width are fabricated, and the conventional HEMT is produced for comparison. With the nanowire channel width decreasing, the threshold voltage of NC‐HEMTs moves positively. Then, the dependence of electron concentration on the nanowire channel width is studied by Silvaco simulation software. With the nanowire channel wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…[8] As the fin width decreases, the ratio of the depletion layer width to the total channel width becomes larger and the threshold voltage is further shifted positively. [9] It can be seen that the saturation current of FinFETs with 160 nm are higher than that of conventional HEMT device at V G = 2 V. The phenomenon mainly stems from the reduction of the source access resistance. [10] While the formation of AlGaN/GaN nano-fins only in the gate opening was reported, the source access region appears as a more ideal source access resistance and the saturation current increases obviously.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[8] As the fin width decreases, the ratio of the depletion layer width to the total channel width becomes larger and the threshold voltage is further shifted positively. [9] It can be seen that the saturation current of FinFETs with 160 nm are higher than that of conventional HEMT device at V G = 2 V. The phenomenon mainly stems from the reduction of the source access resistance. [10] While the formation of AlGaN/GaN nano-fins only in the gate opening was reported, the source access region appears as a more ideal source access resistance and the saturation current increases obviously.…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, with the fin width increasing, the variation of threshold voltage after recessed-gate is increasing, which agrees with the experimental data in the Table 1. Taking into account the effect of side gate to the channel, the N 2DR of FinFET can be given by [9] N…”
Section: Simulation and Modelingmentioning
confidence: 99%
“…For the fin structure, as the piezoelectric polarization will change, the σðxÞ will also be affected. According to the reference, [23] the σðxÞ of the fin structure can be expressed as Formula 5.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Y. He et al and M. Zhang et al have reported fin‐shaped AlGaN/GaN‐based non‐planner HEMT (FinHEMT) structures and modeled threshold voltage by considering fin width (WFin$$ {W}_{\mathrm{Fin}} $$) into consideration along with fin height (HFin$$ {H}_{\mathrm{Fin}} $$) as a fitting parameter 12,13 . Similarly, Ren et al reported a compact model for electrical parameters like threshold voltage and drain characteristics of AlGaN/GaN metal insulator semiconductor (MIS) FinHEMT by incorporating 2‐Dimensional Poisson's equation in the GaN channel region while taking both strain reduction and metal‐GaN depletion effect due to WFin.$$ {W}_{\mathrm{Fin}}.…”
Section: Introductionmentioning
confidence: 99%